SEMANTIC FEATURES OF TERMS RELATED TO VOCATIONAL EDUCATION IN UZBEK AND FRENCH LANGUAGES (World Bulletin of Social Sciences, 2025)
The article discusses terms in linguistics, terminology, and terms related to professional fields. It reveals the process of transition from the general linguistic meaning to a specialized meaning for terms related to vocational education in the Uzbek and French languages, as well as the features of semantic narrowing and specialization. Additionally, based on the semantic grouping of terms, their internal system, semantic similarities and differences are highlighted from a comparative perspective